PENGARUH CAMPUR KODE DALAM EKSPRESI GENERASI Z PADA KOMUNIKASI SEHARI-SEHARI - Ainnun Rahmania; Gisela Tresnawati; Silvia Nurlatipah; Siti Nurkamila; Iis Lisnawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
Language serves as a fundamental tool for expressing ideas and emotions in daily life. With the progression of globalization and technological innovation, code-mixing has become increasingly prevalent, particularly among Generation Z. This study aims to examine the influence of code-mixing on the daily communication expressions of Generation Z. A qualitative research method was applied, utilizing content analysis based on questionnaire data collected from young respondents. The results revealed that many Generation Z individuals actively incorporate code-mixing into their oral and written communication, especially through social media platforms. In formal settings such as presentations and seminars, some respondents indicated a tendency to use code-mixing, while others preferred maintaining linguistic formality. Several participants viewed code-mixing as an important means of expressing themselves more flexibly, whereas others considered it unnecessary in everyday communication. These findings suggest that code-mixing has become an integral part of Generation Z’s linguistic identity, though there remains an awareness of the need to uphold linguistic politeness and preserve the national language. This study emphasizes the importance of balancing global adaptation with the preservation of local cultural values in language use.